2021
DOI: 10.1016/j.plabm.2021.e00252
|View full text |Cite
|
Sign up to set email alerts
|

The „EPiQ“-Study (Evaluation of preanalytical quality): S-Monovette® in manual aspiration mode drastically reduces hemolytic samples in head-to-head study

Abstract: Background Hemolytic blood samples are the number one cause for specimen rejection at emergency departments. Triggered by unsuitable blood sampling material or incorrect handling and a related strong vacuum force, hemolytic samples often must be retaken. The objective of this study was to assess whether correct manual aspiration using S-Monovette® could reduce the number of hemolytic samples. Methods Between January and April 2019, a head-to-head study was conducted. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Statistically significant reduction in serum K and LDH levels were also demonstrated ( Table 2 ). Similar findings have been demonstrated by other groups which have shown marked improvement in rates of hemolysis of blood drawn from IV catheters when the conventional vacuum blood collection system is replaced with the S-Monovette® blood collection system used in aspiration mode [ 13 , 17 , 21 ]. A study conducted to an ED in Italy showed a decrease of sample hemolysis rates from 29% to 2% after the introduction of the S-Monovette® blood collection system for blood drawn from intravenous catheters [ 13 ].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Statistically significant reduction in serum K and LDH levels were also demonstrated ( Table 2 ). Similar findings have been demonstrated by other groups which have shown marked improvement in rates of hemolysis of blood drawn from IV catheters when the conventional vacuum blood collection system is replaced with the S-Monovette® blood collection system used in aspiration mode [ 13 , 17 , 21 ]. A study conducted to an ED in Italy showed a decrease of sample hemolysis rates from 29% to 2% after the introduction of the S-Monovette® blood collection system for blood drawn from intravenous catheters [ 13 ].…”
Section: Discussionsupporting
confidence: 85%
“…A study conducted to an ED in Italy showed a decrease of sample hemolysis rates from 29% to 2% after the introduction of the S-Monovette® blood collection system for blood drawn from intravenous catheters [ 13 ]. In a more recent “EPiQ” study done in an ED in Switzerland with 4794 subjects, introduction of the S-Monovette® system in place of the BD Vacutainer® SST II, resulted in the hemolysis rate of blood samples (HI > 30 mg/dL) to be reduced drastically (17.0%–4.3%) [ 17 ]. Both studies employed a cross-over design [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The blood samples were collected in the morning, directly into 1 mL gasometric syringes (calcium-balanced lithium heparin, The Blood Gas Monovette® 1 ml Sarstedt, Nümbrecht, Germany) by manual aspiration. We decided to use this device to avoid hemolysis influencing the obtained results 25 . The air was removed by attaching a ventilation device and expelling the air from the syringe.…”
Section: Methodsmentioning
confidence: 99%